Legal Review of Breach of Performance Law on Binding Agreement Deeds sale and Purchase of Land and Buildings Made By a Notary - Pambudi, Hayuningtyas; Witasari, Aryani (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine and analyze the default on the deed of sale and purchase agreement and to determine and analyze the settlement of default on the deed of sale and purchase agreement. The approach method used in this study is normative legal, the type of research used in this study is normative legal research, the type and source of data used is normative legal research, using the method of collecting primary legal materials, and the legal materials obtained will be analyzed qualitatively. The results of this study indicate that the sale and purchase agreement cannot always run according to the agreement desired by the parties. Sometimes in practice one of the parties in a sale and purchase agreement does not fulfill the promised performance so that according to the law it is considered to have deviated from the agreement which results in a loss for the other party called default. And legal settlement in the case of default on the Sale and Purchase Agreement can be done in 2 (two) ways, namely non-litigation dispute resolution or outside the court by means of arbitration, negotiation, mediation, and conciliation. As well as litigation settlement through the general court process.Keywords: Notary, Sale and Purchase Agreement, Default